The Administration of the Student Support System of Rajaprajanugroh School under the Office of Special Education Administration Group 8 - Siammai, Natthakarn; Kheowvongsri, Sajanun (Journal of Buddhist Education and Research (JBER), 2025)
This research article aimed to: 1) to examine the management of student support systems in Rajaprajanugroh Schools under the Special Education Administration Bureau, Group 8. 2) compare the management of student support systems in these schools based on gender, educational level, work experience, and individual schools; and 3) collect recommendations for improving the management of student support systems based on teachers’ opinions. The sample group consisted of 208 teachers, and a questionnaire was used as the research instrument, with an overall reliability coefficient of 0.968. Statistical methods used for data analysis included percentage, mean, standard deviation (S.D.), t-test, and F-test. The results are as follows: 1. the overall management of the student care and support system in Rajaprajanugroh Schools under the Office of Special Education Administration, Group 8, was at a high level (𝑥̅ = 4.33, S.D. = 0.64). When analyzed by aspect, the three highest-rated aspects were student promotion and development, prevention and problem-solving, and student referral. 2. The comparison of student care and support system management based on gender, education level, work experience, and individual Rajaprajanugroh schools showed that differences in gender and education level were statistically significant at the 0.05 level. Differences in work experience, both overall and in individual aspects, were not statistically significant. However, differences among Rajaprajanugroh schools were statistically significant at the 0.01 level. 3. The recommendations gathered suggested that administrators should implement real-time monitoring systems to track students’ at-risk behaviors, allowing teachers to respond promptly to situations. Additionally, administrators should promote the establishment of Memorandums of Understanding (MOUs) with hospitals, mental health centers, or private organizations to facilitate effective expert intervention. Lastly, administrators should support schools in developing long-term student support networks by collaborating with relevant external organizations.